Integration of Technology Acceptance Model and Information System Success Model to Analyze User Satisfaction and Continuity of Use in Ticket Booking on the "Access By KAI"Application - Ahmad Raihan; Budi Prasetyo (Journal of Advances in Information Systems and Technology, 2025)
Access by KAI is an application that focuses on ordering train ticketswhich was developed and published by PT Kereta Api Indonesia as KAIAccess since 2014. As a train ticket ordering application, the Access byKAI application has around 12,419,711 registered users with a totalnumber of users. There are 6,101,343 active ones. With that many users,the Access by KAI application currently has a rating of 1.6/5 on theAppstore and 2.2/5 on the Playstore (as of December 1, 2023). Based onthe explanatory description, this research aims to find out what variablessupport or influence user satisfaction and intentions to continue using theAccess by KAI application as a train ticket booking application. Thisresearch applies quantitative methods using an integrated informationsystem success model (ISSM) and technology acceptance model (TAM).Data collection in this research was carried out through distributingquestionnaires using Google Form by applying purposive samplingtechniques. The target respondents are Access by KAI application usersaged 17 to 65 years who have experience ordering train tickets on theAccess by KAI application. From the results of distributing thequestionnaire, 234 respondents were obtained, which was then analyzedusing partial least squares - structural equation modeling (PLS-SEM)using SmartPLS 4 software. From the research analysis carried out, theresults were that ten hypotheses were accepted and five hypotheses wererejected.